Meta-Analysis of Genes Associated with Craniofacial Microsomia (CFM) - Baig, Muhammad Haris (Darul Yasin Al Sys, 2025)
Craniofacial microsomia (CFM) is a complex congenital anomaly primarily involving malformations of structures derived from the first and second pharyngeal arches. Increasing evidence suggests that both genetic predispositions and environmental factors contribute to its pathogenesis. This meta-analysis synthesizes current genetic research on CFM to identify key loci and candidate genes implicated in its development, with a particular focus on those regulating neural crest cell (NCC) migration and differentiation, processes essential for normal craniofacial morphogenesis. The analysis incorporates data from multiple population-based studies and highlights eight major and five additional implicated genetic loci associated with CFM, underscoring considerable genetic heterogeneity across ethnic and demographic groups. In addition to core genetic determinants, the review explores the role of modifier genes and gene–environment interactions in shaping phenotypic variability and disease progression. Methodological challenges inherent to genetic meta-analyses, including statistical heterogeneity, incomplete datasets, and model selection are critically evaluated to ensure the robustness of conclusions. The study further addresses ongoing debates regarding the clinical translation of genetic findings, emphasizing the need for rigorous analytical frameworks to mitigate bias and enhance reproducibility. By consolidating and interpreting available genomic data, this meta-analysis contributes to the evolving understanding of CFM and supports the development of improved diagnostic, prognostic, and therapeutic strategies for affected individuals.